PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA KELAS IV DI MIS ISLAMIYAH LONDUT - Wanda Dwi Yandita; Auffah Yumni; Riris Nurkholidah Rambe (Universitas Negeri Medan, 2022)
Abstract: The Effect of Quantum Teaching Learning Model on Learning Outcomes of Class IV Students in Science Subjects at MIS Islamiyah Londut. This study aims to determine 1) Student learning outcomes in the control class using conventional methods in science subjects in class IV MIS Islamiyah Londut 2) Learning outcomes in the experimental class using the quantum teaching learning method in science subjects in class IV MIS Islamiyah Londut 3) The significant effect of the use of the quantum teaching learning model on learning outcomes in science subjects in class IV MIS Islamiyah Londut. The research method used is quantitative research with a quasi-experimental type. The population and sample in the study were 15 students in the experimental class and 15 students in the control class. The data analysis used was t-test and post-test. The data analysis used statistical methods. The data in question is data obtained from the validation results of learning tools and research instruments, as well as research results. Based on the results of data analysis, it can be concluded that science learning outcomes after the implementation of the quantum teaching learning model are better than before the implementation of this learning model, namely the average pretest score of 85.79, while the posttest average value of 85.87. After testing the data obtained a significant value of 0.059 <0.05, in the Pretest and Posttest data so that H0 is accepted and Ha is accepted. It can be concluded from the hypothesis test that the science learning outcomes after the Quantum Taeching learning model is applied are better than the previous model.